Cytokine Production and NET Formation by Monosodium Urate-Activated Human Neutrophils Involves Early and Late Events, and Requires Upstream TAK1 and Syk - Tatsiy, Olga; Mayer, Thomas Z.; de Carvalho Oliveira, Vanessa; Sylvain-Prévost, Stéphanie; Isabel, Marilyn; Dubois, Claire M.; McDonald, Patrick P. (Frontiers in Immunology, 2020)
Gout is a prevalent and incapacitating disease triggered by the deposition of monosodium urate (MSU) crystals in joints, which are also massively infiltrated by neutrophils. The interaction of the latter with MSU crystals triggers several responses, including the generation of inflammatory mediators and of neutrophil extracellular traps (NETs). Though some of the signaling events mobilized by MSU in neutrophils have been described (e.g. Src family kinases, Syk, PKC, PI3K), the picture remains fragmentary. Likewise, the impact of these signaling events on cellular responses is incompletely understood. In this study, we examined transcriptomic changes triggered by MSU in neutrophils and their impact on the corresponding proteins, as well as the role of various signaling pathways in prominent functional responses. We report for the first time that neutrophils can secrete the monocyte chemoattractant, CCL4, in response to MSU. Accordingly, we found that transcription factors NF-κB, CREB, and C/EBP are belatedly activated by MSU crystals, and at least the former is involved in chemokine generation. Moreover, we show that MAPKs and Akt are activated by MSU in neutrophils, that they are under the control of TAK1 and Syk, and that they participate in cytokine generation and NETosis. In the latter instance, we found the phenomenon to be independent of endogenous ROS, but under the control of PAD4. We finally provide evidence that endogenous factors contribute to the belated phosphorylation of kinases and transcription factors in response to MSU. Collectively, our findings unveil potentially important therapeutic targets for gouty arthritis.